IMPROVING INDONESIAN LANGUAGE LEARNING OUTCOMES USING INQUIRY MODELS IN CLASS IX STUDENTS OF SATAP SUNGAI BERTAM - Susianingsih Susianingsih (Fakultas Bahasa dan Seni UNP, 2019)
Junior high school SATAP Sungai Bertam set KKM indonesian language subject class IX of 78 with the provisions of 100% complete, still very many students who have not reached completeness, the purpose of this research is to increase learning outcome in indonesian language subject in class IX. This research is a classroom action research conducted in two cycles with two learning meetings, which includes: planning, implementation, and reflection, 26 study subjects consisted of 12 males and 14 females, Data collection techniques used a written assessment, observations in the form of indicators of teacher and student success, the results showed that on the pre cycle of percentage of student learning outcomes that is 35%, with the highest 79, the lowerst 50, and the average 66,58, in the first cycle increased by a percentage 73%, with the highest 80, the lowerst 65, and the average 76,27, then in the second cycle is 100% complete with the highest 85, the lowest 80, and the average score 82,81. Based on these results, it can be concluded that inquiry learning model can improve the learning outcomes of grade IX students in indonesian languange subjects at Junior high school SATAP Sungai Bertam.